Inborn Errors of Immunity Presenting with Early-Onset Severe Atopy - Nipat Chuleerarux; Nadia Makkoukdji; Travis Satnarine; Jessica Elise Kuhn; Tanawin Nopsopon; Peerada Valyasevi; Fernanda Bellodi Schmidt; Gary Kleiner; Melissa Gans (Medicina, 2025)
Inborn errors of immunity (IEIs), also known as primary immunodeficiencies, are a group of genetic disorders affecting the development and function of the immune system. While IEIs traditionally present with recurrent infections, an increasing number of cases manifest with early-onset severe atopy, including atopic dermatitis, food allergies, asthma, and allergic rhinitis—features that are often overlooked. This can lead to delayed diagnosis and treatment, which is crucial for IEI patients due to the risk of severe infections. We conducted a literature search and reviewed all IEIs that can present with early-onset severe atopy. The hallmark features of these disorders often include early-onset, persistent, and severe atopic dermatitis, food allergies, and recurrent episodes of asthma, which may be refractory to treatments. Additionally, we discuss the importance of recognizing such severe atopy as a potential indicator of an underlying immune deficiency, particularly when accompanied by unusual infections, growth failure, or autoimmunity. This review aims to raise awareness of this association and emphasize the need for early diagnosis and genetic testing in patients with atypical or treatment-resistant allergic diseases, allowing for more timely diagnosis of underlying immunodeficiencies and appropriate treatments.